Quadrilateral overlapping elements and their use in the AMORE paradigm. (1st October 2019) - Huang, Junbin; Bathe, Klaus-Jürgen
Highlights: We give the formulation of new 4-node overlapping quadrilateral finite elements. The elements are insensitive to mesh distortions. We demonstrate their performance in several numerical examples. We illustrate how the overlapping elements can be utilized in the AMORE scheme of analysis. Abstract: We give the formulation of new 4-node overlapping quadrilateral finite elements and demonstrate their performance in several numerical examples. The elements are insensitive to mesh distortions and lead overall to accurate numerical solutions. We show how the quadrilateral elements are utilized in the AMORE scheme of "a utomaticm eshing witho verlapping andr egulare lements". Since in this paradigm the finite elements interior to the domain of analysis are undistorted regular elements and the distortion-tolerant overlapping elements are used for discretizations near the boundaries, high solution accuracy is achieved. This accuracy is obtained with much less effort for meshing than in traditional finite element analysis and with a reasonable computational expense.